Neuroendocrine Cervical Carcinoma: Karsinoma Serviks Neuroendokrin - Yulian Prastisia; Adrian Djatikusumo; Wina Kanya Wasystha; Iwan Kurnia Effendi (Indonesian Journal of Obstetrics and Gynecology, 2023)
Objective: To present a series of neuroendocrine cervical carcinoma, a rare malignancy of the cervix with different stages, treatment approach and outcome. It is included in this article review about diagnostic approach, treatment and prognosis in dealing with neuroendocrine cervical carcinoma. Methods: Case report Cases: We reported three cases of neuroendocrine cervical carcinoma. First is a 40-year old woman para 2, with stage IIIB neuroendocrine cervical carcinoma and chose palliative care only. Second, a 54-year old woman, para 5 with stage IIB neuroendocrine cervical carcinoma which underwent radiotherapy, with a 4 months disease free period. And lastly, a 36-year old woman, para 2 with stage IB1 neuroendocrine cervical carcinoma, underwent a radical abdominal hysterectomy procedure with pelvic lymphadenectomy and external pelvic radiotherapy. The disease is well controlled and had no recurrence in 15 years. Conclusion: It is important to differentiate neuroendocrine cervical carcinoma with other malignancies that could be found in the cervix. Immunohistochemistry (IHC) tests could be used to achieve that purpose. It is also important to arrange a treatment plan to treat these malignancies and multimodality treatment is preferable for better outcomes. Keywords: Neuroendocrine cervical carcinoma, cervical carcinoma, multimodality treatment.AbstrakTujuan: Melaporkan serangkaian kasus neuroendocrinecervical carcinoma, salah satu jenis keganasan langka padaarea serviks dengan stadium, tata laksana, dan hasil yangberbeda. Dalam artikel ini juga terdapat ulasan mengenaiprosedur diagnosis, manajemen, dan prognosis darineuroendocrine cervical carcinoma.Metode: Laporan kasusKasus: Artikel ini melaporkan tiga kasus. Pertama perempuan40 tahun riwayat partus dua kali dengan karsinoma serviksneuroendokrin stadium IIIB dan hanya memilih perawatanpaliatif. Kasus kedua, perempuan 54 tahun, riwayat partuslima kali dengan karsinoma serviks neuroendokrin stadiumIIB. Pada pasien dilakukan terapi radiasi dan didapatkankondisi bebas penyakit selama 4 bulan. Terakhir, pasienperempuan 36 tahun riwayat partus dua kali dengankarsinoma serviks neuroendokrin stadium 1B1. Dilakukanhisterektomi radikal dan limfadenektomi kelenjar limfepelvis serta terapi radiasi. Kondisi pasien terkontrol dantidak terdapat kekambuhan setelah 15 tahun.Kesimpulan: Karsinoma serviks dengan jenis neuroendokrinharus dibedakan dengan keganasan lain pada daerah serviks.Uji imunohistokimia dapat digunakan untuk membedakanhal tersebut. Selain itu, penyusunan rencana tatalaksanauntuk mengatasi keganasan pada serviks juga harusmenjadi perhatian penting bagi klinisi. Direkomendasikanuntuk menerapkan tata laksana multimodal untuk mencapaihasil terapi yang optimal.Kata kunci: karsinoma serviks, karsinoma serviksneuroendokrin, tata laksana multimodal.